The effect of urbanization on agricultural eco-efficiency and mediation analysis - Zhao, Xiaojing; Yang, Jiamin; Chen, Huijie; Zhang, Xiaoyu; Xi, Yanling (Frontiers in Environmental Science, 2023)
Improving agricultural eco-efficiency (AEE) is a promising way to achieve the sustainability of agricultural development. Although AEE evaluation and driving forces were widely explored, few studies have systematically examined how urbanization, the core driving force, affected AEE. To supplement the existing literature, the GB-US-SBM model was used to assess AEE in China during 2004-2020. Furtherly, it used the mediation effect model to investigate how urbanization influenced the AEE in different agriculture development regions by reducing agricultural labor and changing rural residents’ income. The results showed that: (1) During 2004-2020, China’s AEE revealed a stable improvement, with the mean score increasing from 0.138 to 0.744. Regarding spatial distribution, AEE exhibited a gradient decrease: optimized development region> moderate development region > protected development region. (2) Urbanization had a significantly positive effect on AEE, with the magnitude of the effect greatest in the protected development region, followed by the moderate development region and the optimized development region. (3) The mediator variables, agricultural labor and rural residents’ income, positively mediated the relationship between urbanization and AEE, and the former had a larger mediating effect. Notably, rural residents’ income did not mediate the effect of urbanization on AEE in the protected development region. According to the findings, to improve sustainable agriculture development and urbanization development in China, some policy suggestions were put forward from the aspects of transforming agricultural development mode, accelerating the urbanization process, enhancing vocational education for the middle-aged and young rural labor force, and expanding channels for increasing rural residents’ income.